2020
DOI: 10.1186/s12913-020-05080-1
|View full text |Cite
|
Sign up to set email alerts
|

Medicine shortages and challenges with the procurement process among public sector hospitals in South Africa; findings and implications

Abstract: Background: Medicine shortages are a complex global challenge affecting all countries. This includes South Africa where ongoing medicine shortages are a concern among public sector hospitals as South Africa strives for universal access to healthcare. The objectives of this research were to highlight challenges in the current pharmaceutical procurement process for public sector hospitals. Subsequently, suggest potential ways forward based on the findings as the authorities in South Africa seek to improve the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 27 publications
6
85
1
2
Order By: Relevance
“…Alongside this, introduce programmes if needed to reduce possible shortages of priority medicines and equipment building on experiences in other countries including recommending substitute medicines where suitable acknowledging the risks ( Acosta et al (2019) , Chigome et al (2019) , Miljković et al (2020a) , Miljković et al (2020) , Modisakeng et al (2020) )…”
Section: Resultsmentioning
confidence: 99%
“…Alongside this, introduce programmes if needed to reduce possible shortages of priority medicines and equipment building on experiences in other countries including recommending substitute medicines where suitable acknowledging the risks ( Acosta et al (2019) , Chigome et al (2019) , Miljković et al (2020a) , Miljković et al (2020) , Modisakeng et al (2020) )…”
Section: Resultsmentioning
confidence: 99%
“…There are many studies pointing to the importance of such interventions as envisaged in the strategic reforms in boosting availability of health commodities. 21 27 30 31 For instance, Modisakeng et al 32 concluded that in order to tackle medicines shortages, there was need for ongoing support to provincial pharmacies in South Africa for better contract management and improved data systems to aid inventory management. Similarly, Meyer et al 33 observed that there were a number of initiatives surrounding the availability and access to medicines in the public system in South Africa; many of which focused on early warning systems for the supply of medicines, improvements in data for quantification and forecasting as well as effective contract management.…”
Section: Discussionmentioning
confidence: 99%
“…Medicine shortages are an increasing concern across countries ( Acosta et al, 2019 ) and are a particular issue in Africa where typically up to 94% of its medicines are imported ( N Gage Consulting, 2017 ; Bavier, 2020 ; Dugmore, 2020 ), and supply issues can be exacerbated in countries with ongoing conflicts ( ALCED, 2020 ). However, African countries are already taking steps to address concerns with shortages before and during the pandemic including suggesting potential alternatives ( Chigome et al., 2019 ; Medical Brief, 2020b ; Modisakeng et al., 2020 ; Review Online, 2020 ; Tomlinson, 2020 ). There are also ongoing programmes to address the quality of medicines across Africa.…”
Section: Introductionmentioning
confidence: 99%